2019
DOI: 10.20473/etno.v3i1.12995
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Interactive Metadiscourse in the Abstracts of Articles Written by Indonesian and Nes Scholars

Abstract: An abstract plays an important role in an article because it becomes the face of the whole paper.  Besides, voluntarily or involuntarily when writing an abstract, a writer also applies metadiscourse markers to communicate effectively by organizing, interacting, and showing the stance.  Thus, the application of metadiscourse in an abstract becomes an interesting object to examine.  This study is aimed at examining interactive and interactional metadiscourse suggested by Hyland (2005) in 50 abstracts written by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 17 publications
1
5
0
Order By: Relevance
“…The most frequent resources were 'and', 'because', and 'so'. This result seems consistent with the previous research that found extensive transition markers in abstract writing (Mazidah, 2019;Hamid, 2019). As previously mentioned, frame markers are used to set the structure of an abstract.…”
Section: Figure 1 Percentage Of Metadiscourse Markerssupporting
confidence: 92%
See 1 more Smart Citation
“…The most frequent resources were 'and', 'because', and 'so'. This result seems consistent with the previous research that found extensive transition markers in abstract writing (Mazidah, 2019;Hamid, 2019). As previously mentioned, frame markers are used to set the structure of an abstract.…”
Section: Figure 1 Percentage Of Metadiscourse Markerssupporting
confidence: 92%
“…For example, Kawase (2015) exposed how research article writers employed more metadiscourse markers than thesis writers, arguing the nature of research articles as a professional genre that insists on presenting oneself in the academic world. However, research article and abstract thesis writers used more interactive markers than interactional markers (Ashofteh et al, 2020;Pandey, 2020;Al-Shujairi et al, 2016;Mazidah, 2019). Some other studies reflected how native speakers and non-native speakers of English used metadiscourse markers (Hussein et al, 2018;Kaies, 2019;Nugroho, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Studies on the use of MMs in English RAs by English and Indonesian authors were conducted by Sanjaya et al, (2015) and Mazidah (2019). Sanjaya et al found that English RAs in Applied Linguistics written by English native speakers contain significantly more hedges than those written by Indonesian speakers.…”
Section: Literature Reviewmentioning
confidence: 99%
“…According to Sanjaya et al, this implies that Indonesian scholars badly need instruction in using interactional MMs particularly hedges when writing in English to meet the expectation of English readers. A more recent study on the use of MMs in RAAs was conducted by Mazidah (2019). She compared 50 English RAAs written by Indonesian authors and 50 RAAs written by native English speakers (NESs) in Applied Linguistics.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation